Modified carbon-based adsorption material, preparation method and application in drug adsorption
The preparation of coffee grounds-modified carbon-based adsorbent materials solves the problems of insufficient efficiency, selectivity, and regeneration capacity of existing materials in the treatment of narcotics in waste gas, achieving efficient and low-cost narcotics adsorption, and is suitable for atmospheric environmental monitoring and industrial purification.
Patent Information
- Application Number
- CN202511172059.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-21
- Publication Date
- 2025-12-05
AI Technical Summary
Existing adsorption materials suffer from insufficient efficiency and selectivity, weak regeneration capacity, and high cost in the treatment of toxic substances in waste gas, making it difficult to meet the requirements of efficient and selective adsorption and easy regeneration.
Using inexpensive and readily available coffee grounds as raw material, a modified carbon-based adsorbent material with a three-dimensional graphene bio-carbon structure and Fe-Zn bimetallic oxide active sites was prepared through iron-zinc modification and 900℃ pyrolysis process. This improved the specific surface area and mesoporous structure, thereby enhancing the adsorption performance for drugs.
It achieves efficient and selective adsorption of toxic substances in waste gas, with a static adsorption removal rate of 76% to 98% and a dynamic adsorption recovery rate of 50% to 130%. Moreover, it has low material cost and a controllable and scalable preparation process, making it suitable for atmospheric environmental monitoring and industrial waste gas purification.
Smart Images

Figure CN121060458A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of environmental protection and material engineering, and particularly relates to a modified carbon-based adsorption material for efficiently adsorbing toxic substances in the atmosphere, a preparation method thereof and an application method thereof. BACKGROUND
[0002] Current treatment of toxic substances in waste gas mainly relies on adsorption technology, but there are three major bottlenecks in existing materials: (1) insufficient efficiency and selectivity. Although the specific surface area of traditional activated carbon is high, the surface chemical properties are single, and the affinity for toxic substance molecules is weak. Although the selectivity of materials such as molecular sieves and kaolin can be improved by modification, the matching degree of pore size and toxic substance molecule dynamic diameter is poor, and the dynamic adsorption capacity is less than 5 mg / g. (2) Weak regeneration capacity. Most of the existing materials rely on physical adsorption, and high temperature or strong solvent is required for desorption, which leads to structure collapse. The active sites of chemically modified materials are easily poisoned and deactivated, and the regeneration rate is less than 60%. (3) Cost and scale obstacles. The synthesis of high-performance materials such as metal organic frameworks (MOFs) requires noble metals, and the cost of a single product is more than 1,000 yuan, which is difficult to promote industrially. Although the cost of biochar material is low, the specific surface area of the original sample is small and the surface functional groups are poor, which cannot meet the adsorption demand. Therefore, it is urgent to develop a new type of adsorption material with low cost, high adsorption capacity and easy regeneration, which can efficiently and selectively adsorb toxic substances in waste gas and has good regeneration capacity. SUMMARY
[0003] In order to overcome the above-mentioned technical problems, the purpose of the present application is to provide a modified carbon-based adsorption material with low cost, high adsorption capacity and easy regeneration, which can be used for adsorption of toxic substances in waste gas. The purpose of the present application is to provide a preparation method of a modified carbon-based adsorption material for adsorption of toxic substances in waste gas. The purpose of the present application is to provide a method for application of the modified carbon-based adsorption material in adsorption of toxic substances in waste gas. The inventive concept of the present application is to use cheap and readily available coffee grounds as raw material, and to optimize the modification and pyrolysis process to prepare an adsorption material with high specific surface area, reasonable pore structure and excellent toxic substance adsorption performance, thereby effectively solving the problems of the prior art.
[0004] In order to achieve the above-mentioned purposes, the present application provides a modified carbon-based adsorption material, which uses coffee grounds as raw material, and the coffee grounds are modified by iron and zinc and pyrolyzed to prepare the modified carbon-based adsorption material. The modified carbon-based adsorption material has a three-dimensional graphene biochar structure, and the carbon skeleton is embedded with Fe-Zn bimetallic oxide active sites, and the carbon skeleton has mesopores. The specific surface area of the modified carbon-based adsorption material is greater than 421 m 2 / g, and the average removal rate of static adsorption of toxic substances in waste gas is greater than 85%.
[0005] Further, in the modified carbon-based adsorption material provided by the application, FeCl3·6H2O and ZnCl2 are mixed to form a mixed solution for iron-zinc modification.
[0006] Further, in the modified carbon-based adsorption material provided by the application, the molar ratio of Fe to Zn in the mixed solution is 1:2.
[0007] Further, in the modified carbon-based adsorption material provided by the application, the pyrolysis temperature is 900℃.
[0008] The application further provides a preparation method of any of the modified carbon-based adsorption materials, comprising the steps of:
[0009] S1: Pretreatment of coffee grounds raw materials: the coffee grounds are washed with deionized water until neutral, dried to a moisture content of less than 5%, crushed, sieved to remove impurities, and prepared for use;
[0010] S2: Iron-zinc modification: FeCl3·6H2O and ZnCl2 are mixed to form a modified mixed solution; the pretreated coffee grounds and the prepared modified mixed solution are mixed at a solid-liquid ratio of 1:10 to 1:20, ultrasonically treated, and then left to stand, filtered, washed with deionized water, and dried to constant weight to obtain a brown-yellow granular modified carbon-based adsorption material precursor, the moisture content of the modified carbon-based adsorption material precursor being not higher than 8%;
[0011] S3: Pyrolysis to obtain a modified carbon-based adsorption material: the obtained brown-yellow granular modified carbon-based adsorption material precursor is placed in a tube furnace, heated to a certain temperature, and kept at the temperature, and after the heat preservation is completed, nitrogen is continuously passed until the tube furnace naturally cools to room temperature to obtain a modified carbon-based adsorption material;
[0012] S4: Treatment to obtain an optimized modified carbon-based adsorption material: the dried modified carbon-based adsorption material obtained in the previous step is washed with HCl to remove impurities, and then washed with water until neutral and dried to obtain a black powder-shaped optimized modified carbon-based adsorption material that can be applied.
[0013] Further, in the preparation method of the modified carbon-based adsorption material provided by the application, in the S2 "iron-zinc modification" step, the molar ratio of Fe to Zn in the modified mixed solution is 1:2.
[0014] Further, in the preparation method of the modified carbon-based adsorption material provided by the application, in the S3 "pyrolysis" step, the temperature is raised to 900℃ at a heating rate of 5-10℃ / min, and kept for 2-3h.
[0015] In addition, the application also provides an application method of any of the modified carbon-based adsorption materials or the modified carbon-based adsorption material prepared by any of the preparation methods in the adsorption of toxic substances in waste gas, comprising the steps of:
[0016] S1: Preparation of water-borne graphite powder absorbent: The optimized modified carbon-based adsorbent material and graphite powder are mixed in proportion, put into the absorption tank, and an appropriate amount of water or matching absorbent is added to prepare water-borne graphite powder absorbent.
[0017] S2: Contact between exhaust gas and absorbent liquid: The exhaust gas containing toxic substances is evenly introduced into the bottom of the absorption tank through a gas distribution device, so that the exhaust gas can fully contact the water-borne graphite powder absorbent liquid.
[0018] S3: Adsorption of toxic substances in exhaust gas: Start the stirring device and maintain an appropriate stirring speed to ensure that the graphite powder is evenly dispersed in the absorbent liquid, thereby enhancing the adsorption effect with toxic substances in the exhaust gas.
[0019] Furthermore, in the method for applying modified carbon-based adsorbent material to adsorb toxic substances in waste gas provided by the present invention, in the above-mentioned step S1 "preparation of water-borne graphite powder absorbent", the optimized modified carbon-based adsorbent material is mixed with graphite powder at a mass ratio of 1:1 to 1:5.
[0020] Furthermore, in the method for applying modified carbon-based adsorbent material to adsorb toxic substances in waste gas provided by the present invention, in the above-mentioned step S1 "preparation of water-borne graphite powder absorbent", after the adsorbent is added to the absorption tank, water or phosphate buffer solution with pH 7-9 is added, and the solid-liquid concentration of the solid adsorbent and the buffer solution is 5-10 g / L.
[0021] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) The raw materials are cheap and readily available. Coffee grounds are widely available and inexpensive, and have abundant organic matter and porous structure, which is conducive to the preparation of high-performance carbon-based adsorbent materials. Using coffee grounds as raw materials realizes the resource utilization of waste and reduces the material preparation cost. (2) Excellent adsorption performance. The modified carbon-based adsorbent material prepared has a three-dimensional graphene biocarbon structure with a specific surface area of 421.6935 m². 2 / g, the carbon skeleton is embedded with Fe-Zn bimetallic oxide active sites, the carbon skeleton has mesopores, and the mesopores are uniform. The static adsorption removal rate of drugs in the waste gas is 76% to 98%, and the recovery rate of most target substances in dynamic adsorption meets the method verification standard of 50% to 130%. (3) The preparation process is controllable and scalable. By optimizing the iron-zinc ratio (1:2) and the pyrolysis temperature (900℃), the microstructure and adsorption performance of the material can be stably controlled, with good repeatability. The optimized carbon-based material has a larger specific surface area and richer pore structure, which can significantly improve the adsorption efficiency of drugs in the waste gas. Through modification treatment, the carbon-based material has a stronger affinity for drug molecules and can achieve selective adsorption. (4) Wide range of applications. It can be used for drug capture at atmospheric environmental monitoring points, industrial waste gas purification and other scenarios. It can also be used in conjunction with water-borne graphite powder waste gas purification device to improve purification efficiency through gas-liquid-liquid-solid synergistic effect. By precisely controlling the pretreatment of coffee grounds, iron-zinc modification, and pyrolysis at 900℃, a carbon-based material was prepared with high specific surface area, uniform mesoporous structure, and excellent adsorption performance. Moreover, the raw material cost is low and the preparation process can be scaled up, providing a feasible solution for the efficient removal of toxic substances from the atmosphere and industrial waste gas. Attached Figure Description
[0022] Figure 1 This is a TEM image of the layered structure of the adsorbent material prepared in Example 1;
[0023] Figure 2 FeSEM porous morphology image of the adsorbent material prepared in Example 1;
[0024] Figure 3 The iron-zinc ratio-adsorption capacity relationship curve in Example 2;
[0025] Figure 4 The following are BET specific surface area diagrams of the materials at different pyrolysis temperatures in Example 3: a) 500℃, b) 600℃, c) 700℃, d) 800℃, e) 900℃, f) Comparison diagram of BET specific surface area of the materials at different pyrolysis temperatures.
[0026] Figure 5 The adsorption capacity-time curves of the modified carbon-based adsorbents prepared at different pyrolysis temperatures in Example 3 are shown.
[0027] Figure 6 The pseudo-first-order kinetic fitting lines are for the modified carbon-based adsorbents prepared at different pyrolysis temperatures in Example 3;
[0028] Figure 7 The pseudo-second-order kinetic fitting lines are for the modified carbon-based adsorbents prepared at different pyrolysis temperatures in Example 3. Detailed Implementation
[0029] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. All other embodiments obtained by those skilled in the art without innovative effort are within the scope of protection of the present invention. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.
[0030] A modified carbon-based adsorbent material for efficient adsorption of toxic substances in waste gas is prepared from inexpensive, readily available, and carbon-rich coffee grounds through pretreatment, iron-zinc modification, and high-temperature pyrolysis at 900℃. The preparation method includes the following steps:
[0031] Step 1: Raw material pretreatment. Wash the coffee grounds with deionized water until neutral, dry them in an oven at 60-80℃ for 12-24 hours, then grind them with a grinder and pass them through a 100-200 mesh sieve to remove impurities for later use.
[0032] Step 2: Iron-Zinc Modification. FeCl3·6H2O and ZnCl2 were mixed at a Fe:Zn molar ratio of 1:2 to prepare a modified mixture. Pretreated coffee grounds were added to the modified mixture at a solid-liquid ratio of 1:10 to 1:20 and ultrasonicated at 30–40°C for 2–4 hours (power 300–500W), then allowed to stand for 12–24 hours. After filtration, the solid product was dried in an oven at 60–80°C to constant weight to obtain a modified carbon-based adsorbent precursor with a water content not exceeding 8%, appearing as brownish-yellow granules.
[0033] Step 3: High-temperature pyrolysis. The dried modified sample is placed in a heat-resistant container and then placed in a tube furnace. Nitrogen gas is introduced (flow rate 100–200 mL / min) to purge air. The temperature is then increased to 900°C at a rate of 5–10°C / min and held at this temperature for 2–3 hours. After pyrolysis, the sample is naturally cooled to room temperature under nitrogen protection to obtain the modified carbon-based adsorbent material.
[0034] Step 4: Wash the dried modified carbon-based adsorbent material with HCl to remove impurities, then wash it with water until neutral and dry it to obtain the optimized modified carbon-based adsorbent material, which can be used for the adsorption of toxic substances in waste gas.
[0035] The inventors of this invention discovered through experiments that the adsorption effect is better when the amount of zinc added is greater than that of iron; the iron-zinc ratio with the best adsorption effect is 1:2. This ratio can significantly improve the surface properties and chemical structure of carbon-based adsorbent materials, thereby enhancing their adsorption capacity for drugs.
[0036] The inventors of this invention also discovered through experiments that: a high temperature of 900℃ can promote the carbonization of coffee grounds to form a three-dimensional graphene structure, resulting in a shrinkage of the interlayer spacing; Fe-Zn bimetallic particles are transformed into metal oxide nanoparticles during pyrolysis, which are embedded in the carbon skeleton to form active sites, thereby enhancing the chemical adsorption of drug molecules.
[0037] The optimized modified carbon-based adsorbent obtained by the above preparation method has a wide range of applications. It can be used for drug capture at atmospheric environmental monitoring points, industrial waste gas purification, and can also be used in conjunction with a water-borne graphite powder waste gas purification device. The application method of using it in conjunction with water-borne graphite powder includes the following steps: (1) Mix the optimized modified carbon-based adsorbent with graphite powder in a certain proportion, put it into a water-borne graphite powder absorption tank, add an appropriate amount of clean water or matching absorbent, and make a water-borne graphite powder absorption liquid. (2) Introduce the waste gas containing drugs evenly into the bottom of the absorption tank through a gas distribution device so that the waste gas and the absorption liquid can be fully contacted. (3) Start the stirring device and maintain an appropriate stirring speed so that the graphite powder is evenly dispersed in the absorption liquid, thereby enhancing its adsorption effect on drugs in the waste gas.
[0038] The inventors discovered that the optimal adsorption effect is achieved when the optimized modified carbon-based adsorbent material is mixed with graphite powder at a mass ratio of 1:1 to 1:5.
[0039] The inventors discovered that adding water or a phosphate buffer solution with pH 7-9 to the absorption tank of the purification device after the mixed adsorbent is added, and controlling the solid-liquid concentration to 5-10 g / L, can enhance the capture ability of the modified carbon-based adsorbent material optimized in this invention for water-soluble drugs.
[0040] Example 1
[0041] Raw materials: Commercially available coffee grounds, sourced from a chain coffee shop, are used. The main component is roasted coffee bean residue with a moisture content of approximately 65%, and its main components are cellulose, hemicellulose, and lignin. The preparation method of the modified carbon-based adsorbent material includes the following steps.
[0042] Step 1: Pre-treatment of coffee grounds. Take 500g of coffee grounds and rinse three times with deionized water to remove soluble impurities such as sugar and oil adhering to the surface of the coffee grounds, and stabilize the pH of the rinsing solution at 6.5-7.0. Spread the washed coffee grounds evenly on a tray (thickness ≤2cm) and place them in a 70℃ forced-air drying oven to dry for 20 hours, turning them over every 5 hours to ensure uniform drying, with the final moisture content controlled below 5%. Then, pulverize the dried coffee grounds at a speed of 3000 rpm for 3-5 minutes. After pulverizing, pass the grounds through a 150-mesh standard sieve, collect the sieve-passing material, and store it in a sealed bag in a desiccator.
[0043] Step 2: Modify coffee grounds with iron and zinc to obtain carbon framework precursor products. Prepare a modification solution by mixing FeCl3·6H2O and ZnCl2 at a Fe:Zn molar ratio of 1:2. Take a certain amount of pretreated coffee grounds powder and add it to the modification solution at a solid-liquid ratio of 1:10 to 1:20. Transfer the mixture to an ultrasonic cleaner and sonicate it in a constant temperature water bath at 30–40°C for 2–4 hours, manually shaking the container every 30 minutes to ensure thorough particle dispersion. After completion, allow the mixture to stand at room temperature for 12–24 hours. Collect the solid product by vacuum filtration and wash it 2–3 times with deionized water. Dry the solid product in a 70°C forced-air drying oven for 12 hours to obtain the carbon framework precursor material, which appears as brownish-yellow granules with a moisture content ≤8%.
[0044] Step 3: The modified carbon framework precursor product is pyrolyzed at high temperature to obtain the modified carbon-based adsorbent material. The obtained carbon framework precursor material is dried at 105℃, placed in a tube furnace, and nitrogen is introduced to purge air. Then, the temperature is increased to 900℃ at a rate of 5-10℃ / min and held for 2-3 hours. After the holding period, the heating device is turned off, and nitrogen is continued to be introduced until the tube furnace cools naturally to room temperature to obtain the modified carbon-based adsorbent material.
[0045] Step 4: After removing impurities, the material is dried to obtain the optimized modified carbon-based adsorbent material. The modified carbon-based adsorbent material obtained by pyrolysis is washed three times with 1 mol / L HCl to remove metal oxide impurities; it is then washed with ultrapure water until neutral, and dried at 80℃ for 12 h to obtain a black powder material, which is the optimized modified carbon-based adsorbent material.
[0046] The microstructure of the modified adsorbent material prepared in Example 1 was observed using transmission electron microscopy. Figure 1 The left side shows the modified adsorbent material prepared in Example 1, and the right side shows the unmodified adsorbent material used for comparison. Their surface morphology was observed using field emission scanning electron microscopy. Figure 2 The left side shows the unmodified adsorbent material used for comparison, and the right side shows the modified adsorbent material prepared in Example 1.
[0047] from Figure 1 The TEM images show that the prepared modified carbon-based adsorbent material has a distinct layered structure with an interlayer spacing of approximately 0.18 nm. Compared with the unmodified coffee carbon-based adsorbent material, the interlayer spacing is significantly reduced, which leads to a substantial increase in surface area.
[0048] from Figure 2The FeSEM images show that the modified carbon-based adsorbent material prepared in Example 1 has a sheet-like stacked structure with a porous structure, exhibiting obvious three-dimensional graphene biocarbon structure characteristics, and the carbon skeleton has obvious bimetallic oxide active sites embedded in it; compared with the unmodified biocarbon material, the specific surface area is significantly improved.
[0049] Example 2
[0050] To investigate the effect of the molar ratio of Fe to Zn on the performance of the modified carbon-based adsorbent materials prepared in this invention, FeCl3 and ZnCl2 mixed solutions with molar ratios of 0:0, 0.1:0.1, 0.5:0.5, 1:0, 0:1, 1:1.5, 1.5:1, 1:2, 2:1, and 2:2 were prepared. The pretreated material from step one of Example 1 was added to these solutions at solid-liquid ratios of 1:10 to 1:20. The mixture was then transferred to an ultrasonic cleaner and ultrasonically treated in a constant temperature water bath at 30–40°C for 2–4 hours, with manual shaking every 30 minutes to ensure thorough particle dispersion. After treatment, the mixture was allowed to stand at room temperature for 12–24 hours. The solid product was collected by vacuum filtration and washed 2–3 times with deionized water. The solid product was dried in a 70°C forced-air drying oven for 12 hours, followed by pyrolysis at 900°C under a N2 atmosphere to obtain a series of iron-zinc modified carbon-based adsorbent materials. A target pollutant solution of a certain concentration was prepared. 50 mL of each solution was placed in a stoppered conical flask, and 0.05 g of modified carbon-based adsorbent material with different iron-zinc ratios was added. The flask was then placed in a constant-temperature shaker. After the shaker was completed, samples were taken, and the pollutant concentration was determined using high-performance liquid chromatography (HPLC). The iron-zinc ratio-adsorption capacity relationship curve is shown below. Figure 3 .
[0051] Depend on Figure 3 It can be seen that when the amount of zinc added is greater than that of iron, the modified carbon-based adsorbent material has a better adsorption effect; when Fe:Zn=1:2, the bimetallic synergistic effect is the best, and the adsorption capacity of the modified carbon-based adsorbent material is the largest, exceeding 140mg / g.
[0052] Example 3
[0053] To investigate the effect of pyrolysis temperature on the performance of the modified carbon-based adsorbent materials obtained in this invention, the material obtained in step two of Example 1 was dried at 105°C, placed in a tube furnace, and then heated to 500°C, 600°C, 700°C, 800°C, and 900°C respectively at a heating rate of 5–10°C / min, and held at these temperatures for 2–3 hours. After the holding period, the heating device was turned off, and nitrogen gas was continuously purged until the tube furnace naturally cooled to room temperature, thus obtaining modified carbon-based adsorbent materials at different pyrolysis temperatures.
[0054] Specific surface area and pore size analyzers were used, with nitrogen as the adsorbate. Before testing, the samples were degassed at 150℃ for 6 hours to remove surface-adsorbed impurities. A target pollutant solution of a specific concentration was prepared, and 50 mL of each solution was placed in a stoppered conical flask. 0.05 g of the modified carbon-based adsorbent material prepared at different pyrolysis temperatures was added to each flask. The flasks were placed in a constant-temperature shaker, and samples were taken over a time series from 0 to 500 min. The pollutant concentration was detected using high-performance liquid chromatography (HPLC). The BET specific surface area diagrams of the materials at different pyrolysis temperatures are shown in [Figure number missing]. Figure 4 ,in Figure 4 In the figure, (a) represents 500℃, (b) represents 600℃, (c) represents 700℃, (d) represents 800℃, (e) represents 900℃, and (f) is a comparison of the BET specific surface area of the materials at different pyrolysis temperatures.
[0055] Figure 4 The results showed that the modified carbon-based adsorbent material prepared at a pyrolysis temperature of 900℃ had a specific surface area as high as 421.6935 m². 2 / g, compared to 22.3416m at a pyrolysis temperature of 500℃. 2 / g, the value is significantly improved. The adsorption-desorption curve of the prepared modified carbon-based adsorbent material exhibits a type IV isotherm and an H4 hysteresis loop, indicating that the prepared modified carbon-based adsorbent material has a typical mesoporous structure and uniform pore distribution. The pore size of mesopores is larger than that of micropores, with the pore size range of 2–50 nm, while pores with a diameter less than 2 nm are called micropores.
[0056] The adsorption capacity-time curves of the modified carbon-based materials prepared at pyrolysis temperatures of 500℃, 600℃, 700℃, 800℃, and 900℃ are shown in the figure. Figure 5 The pseudo-first-order and pseudo-second-order kinetic fitting lines of the modified carbon-based adsorbents prepared at different pyrolysis temperatures are shown in the figures below. Figure 6 , Figure 7 A high degree of fit to pseudo-first-order kinetics indicates that physical adsorption is dominant, while a high degree of fit to pseudo-second-order kinetics indicates that chemisorption is dominant.
[0057] Combination Figure 5 , Figure 6 and Figure 7 The results show that the modified carbon-based adsorbent material prepared at a pyrolysis temperature of 900℃ is graphene biocarbon with chemically active sites embedded in its framework. It combines both physical and chemical adsorption methods, resulting in a faster adsorption rate and a larger adsorption capacity.
[0058] Example 4
[0059] After preparing the modified carbon-based adsorbent material in Example 1, a feasible method of application needs to be found in order to apply this material to drug adsorption. This example designs a static adsorption test method to examine the static adsorption effect of the modified carbon-based adsorbent material prepared in Example 1 on 18 kinds of drugs. The static adsorption test is carried out according to the following steps:
[0060] Step 1: Select 18 common atmospheric toxic substances and precursors, including morphine, codeine, methamphetamine, etc. (see Table 1 for details), and prepare a mixed standard gas of 10 ppb. Set up a closed static adsorption chamber with a built-in gas circulation device; introduce the mixed waste gas into the adsorption chamber.
[0061] Step 2: 0.01g of the modified carbon-based adsorbent material prepared in Example 1 was loaded into the adsorption tube. The adsorption tube was heated for 10 min, then cooled to 25°C and maintained at adsorption equilibrium for 24 h. Finally, the drug components captured by the modified carbon-based adsorbent material in the adsorption tube were analyzed. The removal rates of 18 drugs when 0.01g of the modified carbon-based adsorbent material prepared in Example 1 was loaded are shown in Table 1.
[0062] Table 1. Removal rates of 18 kinds of drugs by adding 0.01g of modified carbon-based adsorbent material prepared in Example 1.
[0063]
[0064]
[0065] Table 1 shows that after reaching adsorption equilibrium, the removal rates of most drugs ranged from 42% to 98%, such as 98.87% for 6-acetylmorphine and 42.9% for tramadol. This indicates that the experimental method is highly reliable. However, since the adsorption-desorption stability of modified carbon-based adsorbent materials varies for drugs with different physicochemical properties, the removal rate can be optimized by adjusting the pore structure and surface chemical properties of the material.
[0066] Example 5
[0067] The inventors previously used water as the tail gas adsorbent, but the low drug recovery rate affected the evaluation of dynamic adsorption performance. To optimize the experimental method, methanol was used as the tail gas adsorbent in this embodiment. The adsorption rate was quickly calculated using a blank control, improving experimental efficiency and data reliability, verifying the feasibility of the method, and providing an efficient testing method for the study of the dynamic adsorption performance of carbon-based materials.
[0068] Nitrogen cylinders provided the carrier gas at a flow rate controlled at 100 mL / min. Simulated waste gas was introduced into an adsorption column filled with 0.1 g of the modified carbon-based adsorbent material prepared in Example 1 for dynamic adsorption. The tail gas was fed into an absorption bottle containing 5 mL of methanol as the experimental group, while an absorption bottle containing 5 mL of ultrapure water served as a blank control group. The removal rates of 18 toxic substances in the tail gas after dynamic adsorption are shown in Table 2.
[0069] Table 2. Removal rates of 18 toxic substances in exhaust gas after dynamic adsorption.
[0070] Serial number Drug name (Chinese / English) Removal rate / % 1 Morphine 61.16122 2 Cathinone 48.97886 3 Codeine 89.33142 4 Methcathinone 49.96287 5 Adenosine monophosphate 54.58592 6 O6-Acetylmorphine 35.12345 7 4,4'-Diaminodiphenylmethane 72.4995 8 F-norketamine 29.787588 9 PMA 65.98103 10 MAMP 58.02394 11 MDMA 83.01787 12 F-ketamine 42.55091 13 PMMA 73.90181 14 Norketamine 33.87837 15 Ketamine 39.02076 16 Tramadol 78.69751 17 Benzoylecgonine 39.84098 18 Cocaine 67.63484
[0071] Table 2 shows that the removal rate of 10 drugs is >50%, of which 5 drugs, including codeine and MDMA, are >70%.
[0072] Example 6
[0073] The inventors designed a method for adsorbing narcotics in waste gas using the modified carbon-based adsorbent material prepared in Example 1. The method is as follows: (1) Mix the optimized modified carbon-based adsorbent material with graphite powder in a certain proportion, put it into a water-borne graphite powder absorption tank, add an appropriate amount of clean water or matching absorbent, and prepare a water-borne graphite powder absorption liquid; (2) Introduce the waste gas containing narcotics evenly to the bottom of the water-borne graphite powder absorption tank through a gas distribution device, so that the waste gas and the absorption liquid are in full contact; (3) Start the stirring device and maintain an appropriate stirring speed to make the graphite powder evenly dispersed in the absorption liquid, thereby enhancing its adsorption effect on the narcotics in the waste gas. Narcotics in waste gas are easily soluble in water, and narcotics dissolved in water are adsorbed by graphite powder evenly dispersed in the water. That is, the effect of purifying waste gas is achieved through the linkage process of gas-liquid absorption and liquid-solid adsorption.
Claims
1. A modified carbon-based adsorbent material using coffee grounds as a raw material, characterized by The coffee grounds are subjected to iron-zinc modification and pyrolysis to form the modified carbon-based adsorption material. The modified carbon-based adsorption material has a three-dimensional graphene bio-carbon structure, and Fe-Zn bimetallic oxide active sites are embedded in the carbon skeleton, and the pores in the carbon skeleton are mesopores. The specific surface area of the modified carbon-based adsorption material is greater than 421 m 2 The static adsorption average removal rate of the modified carbon-based adsorption material for toxic substances in exhaust gas is greater than 85%.
2. The modified carbon-based adsorbent material of claim 1, wherein FeCl3·6H2O and ZnCl2 mixed solution is used for the iron-zinc modification.
3. The modified carbon-based adsorbent material of claim 2, wherein The molar ratio of Fe to Zn in the mixed solution is 1:
2.
4. The modified carbon-based adsorbent material of claim 1, wherein The pyrolysis temperature is 900℃.
5. The method of producing a modified carbon-based adsorbent material according to any one of claims 1 to 4, characterized by The method comprises the following steps: S1: Pretreatment of coffee grounds raw materials: wash the coffee grounds with deionized water until neutral, dry to a moisture content of less than 5%, crush, sieve to remove impurities, and reserve; S2: Iron-zinc modification: mix FeCl3·6H2O and ZnCl2 to form a modified mixed solution; mix the pretreated coffee grounds with the prepared modified mixed solution at a solid-liquid ratio of 1:10 to 1:20, ultrasonic treatment, and then stand, filter, wash with deionized water, and dry to constant weight to obtain a brown-yellow granular modified carbon-based adsorption material precursor, and the water content of the modified carbon-based adsorption material precursor is not higher than 8%; S3: Pyrolysis to obtain a modified carbon-based adsorption material: place the obtained brown-yellow granular modified carbon-based adsorption material precursor in a tube furnace, heat to a certain temperature, and keep the temperature constant, continue to pass nitrogen gas after the temperature keeping is completed until the tube furnace naturally cools to room temperature, and obtain the modified carbon-based adsorption material; S4: Treatment to obtain an optimized modified carbon-based adsorption material: wash the dried modified carbon-based adsorption material obtained in the previous step with HCl to remove impurities; After washing to neutral, dry to obtain a black powder-shaped optimized modified carbon-based adsorption material that can be applied.
6. The method of claim 5, wherein the modified carbon-based adsorbent material is prepared by In the S2"iron-zinc modification" step, the molar ratio of Fe to Zn in the modified mixed solution is 1:
2.
7. The method for preparing a modified carbon-based adsorbent material as described in claim 5, characterized in that... In the S3"pyrolysis" step, the temperature is increased to 900℃ at a rate of 5-10℃ / min, and the temperature is kept constant for 2-3h.
8. Use of the modified carbon-based adsorbent material according to any one of claims 1 to 4 or of the modified carbon-based adsorbent material prepared according to the preparation method of any one of claims 5 to 6 for the adsorption of poisons in exhaust gases, characterized in that The method comprises the following steps: S1: Preparation of water-borne graphite powder absorption liquid: mix the obtained optimized modified carbon-based adsorption material with graphite powder in a certain proportion, put it into an absorption tank, add an appropriate amount of water or matching absorbent, and prepare a water-borne graphite powder absorption liquid; S2: Contact of waste gas with absorption liquid: introduce the waste gas containing toxic substances into the bottom of the absorption tank through a gas distribution device to make the waste gas fully contact with the water-borne graphite powder absorption liquid; S3: Adsorption of toxic substances in waste gas: start the stirring device and keep appropriate stirring speed to make the graphite powder uniformly dispersed in the absorption liquid to enhance the adsorption of toxic substances in the waste gas.
9. The use of a modified carbon-based adsorbent material according to claim 8 for the adsorption of toxic substances from exhaust gases, characterized in that In the S1"preparation of water-borne graphite powder absorption liquid" step, the optimized modified carbon-based adsorption material and the graphite powder are mixed in a mass ratio of 1:1 to 1:
5.
10. The use of a modified carbon-based adsorbent material according to claim 8 for the adsorption of toxic substances from exhaust gases, characterized in that In the S1"preparation of water-borne graphite powder absorption liquid" step, after the absorbent is added to the absorption tank, add water or phosphate buffer solution with a pH of 7-9, and the solid absorbent and the buffer solution have a solid-liquid concentration of 5-10g / L.